2007
DOI: 10.2460/javma.231.9.1390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of twin birth calvings on milk production, reproductive performance, and survival of lactating cows

Abstract: Twin birth was associated with decreased survival, milk production, and reproductive performance. Having at least 1 dead twin was even more detrimental than having live twins and resulted in decreased milk production and reproductive performance of lactating cows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 18 publications
6
41
4
Order By: Relevance
“…Meyer et al (2000) reported that calving difficulty, gestation length of 15 to 12 d below the mean, and male calves were important risk factors for stillbirth. Bicalho et al (2007) and Meyer et al (2001) reported a significant decreasing trend in the incidence of stillbirth by parity in Holstein dairy cows. Also, different studies indicated that male calves had significantly more stillbirths than heifer calves (Mee, 1991;Heins et al, 2006;Ghavi Hossein-Zadeh et al, 2008).…”
Section: Effects Of Main Reproductive and Health Problems On The Perfmentioning
confidence: 96%
See 4 more Smart Citations
“…Meyer et al (2000) reported that calving difficulty, gestation length of 15 to 12 d below the mean, and male calves were important risk factors for stillbirth. Bicalho et al (2007) and Meyer et al (2001) reported a significant decreasing trend in the incidence of stillbirth by parity in Holstein dairy cows. Also, different studies indicated that male calves had significantly more stillbirths than heifer calves (Mee, 1991;Heins et al, 2006;Ghavi Hossein-Zadeh et al, 2008).…”
Section: Effects Of Main Reproductive and Health Problems On The Perfmentioning
confidence: 96%
“…This allows dairy producers to select among their herd's potential dams and produce dairy replacement heifers from only the genetically superior animals and promotes enhanced rates of genetic gains (De Vries et al, 2008). However, most authors today would agree that twin pregnancies are undesirable in a dairy herd (Bicalho et al, 2007;López-Gatius et al, 2009;Andreu-Vázquez et al, 2012). However, twin birth is disadvantageous for most beef and dairy producers because of its association with a number of unfavorable effects, including lower potential calf survival, increased culling rate and poorer cow reproductive performance (Fricke, 2001;Bell & Roberts, 2007;Ghavi Hossein-Zadeh et al, 2008Andreu-Vázquez et al, 2012).…”
Section: Twinningmentioning
confidence: 99%
See 3 more Smart Citations